Strategi Penguatan Daya Saing UMKM Kuliner melalui Sistem Informasi Manajemen : Studi Kasus D’penyet Presto Lunak Ludes D’geprek By Ex Chef Hotel Pangeran - Nur Fitriana; Siti Annisa Nazwa; Nadyya Ghaisani; Riva Lina Nurhusin; Meli Febriyanti; Enjelina Simbolon; Fanny Agustina Siahaan (Politeknik Piksi Ganesha Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy, especially in the highly competitive culinary sector. This service aims to strengthen the competitiveness of culinary MSMEs through the application of Management Information Systems (SIM), with a case study on D'Penyet Presto Lunak Ludes D'Geprek, a business owned by a former chef of Hotel Pangeran. The strategies include training on the use of Buku Warung for financial management, assistance in creating and managing social media accounts such as Instagram and Tik Tok to expand the reach of digital marketing, and registration to the Shopee Food delivery service platform as a partner to expand online sales channels. In terms of visual and brand identity, a logo was created, a menu list was designed, information on the location of the business on Google Maps was updated, and food packaging was changed to make it more attractive. The results showed an increase in digital visibility, operational efficiency, and market expansion. This effort is expected to increase the competitiveness of culinary MSMEs in the face of increasingly fierce industry competition.